Research of efficiency of the organic Rankine cycle on a mathematical model; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Galashov N. N. Nikolay Nikitovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Gabdullina A. I. Albina Ilgizovna; Kiselev A. V. Aleksandr Viktorovich; Melnikov D. V. Denis Vladimirovich (2017, 2017)
Title screen